Meningkatkan Kemampuan Bahasa Anak Melalui Pembelajaran Kooperatif Type Picture and Picture di Kelompok B TK Hanan Al-Fazza - Fransisca Fransisca; Sapri Sapri; Sri Wahyuni (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research was motivated by the lack of language development in children aged 5-6 years in group B of Hanan Al-Fazza Kindergarten. This research aims to determine: 1) Children's language development before using the picture and picture type learning model in group B of Hanan Al-Fazza Kindergarten. 2) How does the child's language develop after using the picture and picture type learning model in group B of Hanan Al-Fazza Kindergarten. 3) What obstacles do children encounter through the picture and picture type learning model? This research was carried out at Hanan Al-Fazza Kindergarten, Percut Sei Tuan subdistrict on February 16 2024 with 15 children studied. This research was carried out with a pre-cycle, followed by cycle I and finally cycle II. Each cycle is held 5 times. Based on the results of research that has been carried out, there is an increase in children's language improvement through the picture and picture type learning model, which was obtained from pre-cycle to cycle II. Where the results obtained pre-cycle showed that the classical percentage of children's language improvement through the typ e-picture and picture learning model was 27%, then in cycle I there was 53% and finally in cycle II there was 80%. With the final results obtained by researchers in the last cycle with a total of 80%, it can be categorized as improving children's language at Hanan Al-Fazza Kindergarten as developing very well.